Implementasi Whistleblowing System dalam Meningkatkan Efektivitas Pengaduan Masyarakat (Studi Pada ACRC Korea) - Muhammad Affandi; Kurniawan, Teguh (Universitas Indo Global Mandiri, 2024)
In disclosing allegations of wrongdoings or corruption, an effective whistleblowing reporting and handling system is required as a form of implementing good corporate governance in public services carried out by the government. By conducting a study on the implementation of the complaint system and whistleblowing system at the Anti-Corruption & Civil Rights Commission of Korea (ACRC), this research aims to determine and analyze the implementation of the whistleblowing system and the factors that influence the effectiveness of complaint management. Through a systematic literature review using PRISMA 2020 and organizational capacity analysis by using Douglas Horton’s theory, it is concluded that a complaints system must be supported by policies and strategies from top management, human resources, technological infrastructure support, monitoring and evaluation processes, and networks as an effort to increase capacity in order to create a complaint handling system and effective policy. In addition, a policy of reward and protection for whistleblowers is needed which supported both internally and through collaboration with other agencies so that whistleblowers feel safe in reporting suspected wrongdoings.